PENDIDIKAN KARAKTER BERBASIS PADA NILAI-NILAI DAN TELADAN NABI MUHAMMAD SAW - ST Rahmah; Laila Rizky; Hendra Supardi (Yayasan Baitul Hikmah al-Zain, 2025)
Education has become the main focus character in the world of education today to develop a generation that has faith, noble character and responsibility. Islamic education and learning the Prophet's sirah is a means of forming a pious person and in accordance with the goals of Indonesian national education. The research outlines the values ​​of character education in sirah nabawiyah learning which can be applied to Muslim individuals. This research methodology uses a qualitative approach with literature study methods used to explore and find a deeper understanding of the values ​​of sirah nabawiyah-based character education. Through learning the Prophet's sirah, it is hoped that we can provide an example for Muslims in everyday life. This research aims to develop a character education model based on sirah nabawiyah, namely an approach that refers to the life and behavior of the Prophet Muhammad as the main example for noble moral education. Sirah Nabawiyah was chosen because it contains noble values ​​that are relevant and applicable to forming the moral character of the younger generation. Based on this background, the research will explain the values ​​of Sirah Nabawiyah-based character education which can be understood and applied as Muslim individuals, teachers, students in the personal, family and other general communities.